Targeting Residual Inflammatory Risk: A Shifting Paradigm for Atherosclerotic Disease - Aday, Aaron W.; Ridker, Paul M. (Frontiers in Cardiovascular Medicine, 2019)
As biologic, epidemiologic, and clinical trial data have demonstrated, inflammation is a key driver of atherosclerosis. Circulating biomarkers of inflammation, including high-sensitivity C-reactive protein (hsCRP) and interleukin-6 (IL-6), are associated with increased risk of cardiovascular events independent of cholesterol and other traditional risk factors. Randomized trials have shown that statins reduce hsCRP, and the magnitude of hsCRP reduction is proportional to the reduction in cardiovascular risk. Additionally, these trials have demonstrated that many individuals remain at increased risk due to persistent elevations in hsCRP despite significant reductions in low-density lipoprotein cholesterol (LDL-C) levels. This “residual inflammatory risk” has increasingly become a viable pharmacologic target. In this review, we summarize the data linking inflammation to atherosclerosis with a particular focus on residual inflammatory risk. Additionally, we detail the results of CANTOS, which showed that directly reducing inflammation with an IL-1 antagonist reduces cardiovascular event rates independent of LDL-C. These positive data are contrasted with neutral evidence from CIRT in which low-dose methotrexate neither reduced the critical IL-1 to IL-6 to CRP pathway of innate immunity, nor reduced cardiovascular event rates.